2015
DOI: 10.1111/jrh.12112
|View full text |Cite
|
Sign up to set email alerts
|

The Rural Obstetric Workforce in US Hospitals: Challenges and Opportunities

Abstract: Purpose The purpose of this study was to describe the types and combinations of clinicians who are delivering babies in rural hospitals, their employment status, the relationship between hospital birth volume and staffing models, and the staffing challenges faced by rural hospitals. Methods We conducted a telephone survey of 306 rural hospitals in 9 states: Colorado, Iowa, Kentucky, New York, North Carolina, Oregon, Vermont, Washington, and Wisconsin, from November 2013-March 2014 to assess their obstetric w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 27 publications
(46 reference statements)
1
81
0
1
Order By: Relevance
“…Previous analysis found that the state-level proportion of rural women with non-local childbirth varied from 18.9% in Vermont to 32.4% in Kentucky. 28 Recognizing that state policies may affect non-local childbirth, we included state-level fixed effects in main models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis found that the state-level proportion of rural women with non-local childbirth varied from 18.9% in Vermont to 32.4% in Kentucky. 28 Recognizing that state policies may affect non-local childbirth, we included state-level fixed effects in main models.…”
Section: Methodsmentioning
confidence: 99%
“…10 The challenge of ensuring that appropriate maternity services are available to meet clinical needs tops the list of concerns among rural obstetric unit managers, medical directors, and clinicians. 11 …”
Section: Introductionmentioning
confidence: 99%
“…524, 2012) but this specialized workforce supply is limited, especially in rural areas. (Kozhimannil et al, 2015; Rosenblatt et al, 2015) State and federal policy can influence clinician supply, as indicated by differential growth in physicians credentialed to provide opioid treatment based on state-level ACA implementation. (Knudsen, Lofwall, Havens, & Walsh, 2015)…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…Recognizing the particular needs of rural residents with opioid‐affected births can inform clinical and policy responses within the rural context, where resources, infrastructure, and health care workforce capacity differ substantially from urban areas . For instance, access to hospital‐based obstetric care is declining in rural United States counties; currently, fewer than half of rural counties have a hospital that provides obstetric services .…”
mentioning
confidence: 99%